2017
DOI: 10.1080/09513590.2017.1399697
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of chronic endometritis macrotypes differentiation among women with reproductive losses

Abstract: To evaluate the prognostic value of a comprehensive endometrial study after early reproductive losses (RL). A group of 306 women with early RL (missed abortion (n = 120), spontaneous miscarriage (n = 120), and ineffective in vitro fertilization attempts (n =66) were prospectively examined up to 6 months after the discharge of the uterus at the hospital bases of the Department of Obstetrics and Gynecology with the Сourse of perinatology at the PFUR Medical Faculty. Hysteroscopic macrotypes differentiation - hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…The resulting material from the two samples was stored at −80 ° C. The sample collection was performed between September 2016 and November 2018. We also performed analysis on CE, as described previously 18 19 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting material from the two samples was stored at −80 ° C. The sample collection was performed between September 2016 and November 2018. We also performed analysis on CE, as described previously 18 19 .…”
Section: Methodsmentioning
confidence: 99%
“…We also performed analysis on CE, as described previously. 18 There is no consensus on the diagnostic criteria to define what accounts for CE and there are seven or more different criteria previously reported. 19 In our study CE was diagnosed based on the presence of one or more plasma cells with positive CD138 immunohistochemistry, as these cells are typically absent in the endometrium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that the concordance rate of hysteroscopy-diagnosed CE and clinico-histopathologic CE was approximately 57.5%-66% 21 , and another investigation determined that the diagnostic accuracy of hysteroscopy (93.4%) was higher than that of histopathologic methods 6 . Identifying the various hysteroscopic features of CE makes it possible to re ne the general description of CE to speci c microscopic manifestations and characteristics 27 . Cicinelli et al 28 proposed new diagnostic criteria for hysteroscopic CE (the Delphi consensus) based on international randomized controlled observations.…”
Section: Discussionmentioning
confidence: 99%
“…Існують різноманітні методи діагностики ХЕ. Доведено можливість діагностики ХЕ за допомогою ультразвукового дослідження, виділено ультразвукові критерії діагностики ХЕ в різні фази менструального циклу [10]. Гістероскопія посідає провідне місце серед діагностичних методів ХЕ.…”
Section: ефективність лікування безпліддя методом запліднення In Vitrunclassified